PENGARUH TINGKAT SUKU BUNGA, CAPITAL ADEQUACY RATIO, NON PERFORMANCE LOANS DAN LOAN TO DEPOSIT RATIO TERHADAP PENYALURAN KREDIT UMKM (Studi Kasus Bank Umum Swasta Nasional Tahun 2014-2016) - Lestari, Indah Sri; Amirah, Mrs. (PERMANA, 2017)
Influence of Interest Rates, Capital Adequacy Ratio, Non Performance Loans And Loan To Deposit Ratio Against MSME Credit Distribution (Case Study of National Private Commercial Banks 2014-2016). The purpose of this study is 1) to determine the effect of interest rates on MSME lending 2) to determine the effect of capital adequacy ratio on MSME lending 3) to determine the effect of non performance loans on MSME lending 4). to determine the effect of loan to deposit ratio on MSME lending, 5) to determine the effect of interest rates, capital adequacy ratios, non-performance loans, and loan to deposit ratio together on MSME lending. The hypothesis in this study is 1) there is an influence of interest rates on MSME lending 2) there is an influence of capital adequacy ratio on MSME lending, 3) there is an effect of non performance loans on MSME lending, 4) there is a loan to deposit ratio effect on distribution MSME loans, 5) there are influences on interest rates, capital adequacy ratios, non-performance loans, and loan to deposit ratios against MSME lending. The method of data collection in this study is the documentation method. The method of data analysis in this study is the classic assumption test, simple regression analysis, test the significance of simple regression, multiple regression analysis, multiple regression test significance, and analysis of the coefficient of determination. The conclusion of this study is 1) there is a negative and significant interest rate effect on MSME lending, as evidenced by the regression equation, namely Ŷ = 5,643-0,026 X1. From the results of the calculation of the significance test obtained sig value of 0.012. Because the sig value of 0.012 <0.05, it can be interpreted that there is a significant influence on the interest rate on MSME lending together. 2) there is a positive influence and a significant capital adequacy ratio to MSME lending, as evidenced by the regression equation, namely Ŷ = 4.966 + 0.024 X2. From the results of the calculation of the significance test obtained sig value of 0.003. Because the sig value 0.003 <0.05 can be interpreted that there is a significant effect of capital adequacy ratio on the distribution of MSME loans together. 3) there is a positive and not significant effect on non performance loans on MSME lending, as evidenced by the regression equation, namely Ŷ = 5.433 + 0.010 X3. From the results of the calculation of the significance test, the sig value is 0.183. Because the sig value of 0.183> 0.05 can be interpreted that there is no significant effect of non-performance loans on MSME loan disbursement together. 4) there is a positive and insignificant influence of loan to deposit ratio on MSME lending, as evidenced by the regression equation, namely Ŷ = 4,599 + 0,010 X4. From the results of the calculation of the significance test, the sig value is 0.306. Because the sig value is 0.306> 0.05, it can be interpreted that there is no significant effect of loan to deposit ratio on MSME lending together. 5) there is a positive and significant influence of interest rates, capital adequacy ratios, non performance loans, and loan to deposit ratio together towards MSME lending, as evidenced by the regression equation, namely Ŷ = 4,660 + 0,008 X1 + 0,028 X2 + 0,007 X3 + 0,002 X4. From the calculation results obtained a significance value of multiple regression coefficients 0.049 <0.05, meaning that there is a significant effect of interest rates, capital adequacy ratios, non performance loans, and loan to deposit ratio together towards MSME lending to National Private PUBLIC Banks Year 2014-2016 together. Keywords: Interest Rate, Capital Adequacy Ratio, Non Performing Loan, Loan to eposit Ratio, MSME Credit Distribution.